Clinical Problem Solving and Using New Paths in the Laboratory: Learning from Case Studies - Lämmle, Bernhard (Hämostaseologie, 2020)
Three selected casuistic studies of individual patient problems from my long-standing professional experience are presented. I intend to highlight the potential contribution of case studies, including new approaches of laboratory investigation, for the advancement of pathophysiological knowledge and would encourage to “rehabilitate” the low academic profile generally attributed to “case reports.”
Keywords: bleeding complications; vitamin K antagonist; F9 propeptide mutation; congenital; autoimmune; thrombotic thrombocytopenic purpura; ADAMTS13; patent ductus arteriosus; case reports